2019
DOI: 10.1073/pnas.1914395116
|View full text |Cite
|
Sign up to set email alerts
|

T6SS and ExoA of flesh-eating Aeromonas hydrophila in peritonitis and necrotizing fasciitis during mono- and polymicrobial infections

Abstract: An earlier report described a human case of necrotizing fasciitis (NF) caused by mixed infection with 4 Aeromonas hydrophila strains (NF1–NF4). While the NF2, NF3, and NF4 strains were clonal and possessed exotoxin A (ExoA), the NF1 strain was determined to be phylogenetically distinct, harboring a unique type 6 secretion system (T6SS) effector (TseC). During NF1 and NF2 mixed infection, only NF1 disseminated, while NF2 was rapidly killed by a contact-dependent mechanism and macrophage phagocytosis, as was dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 42 publications
(67 reference statements)
1
25
0
Order By: Relevance
“…They suggested that the type six secretion system (T6SS) and exotoxin A (ExoA) were involved in this complex infection. Recently, using a mouse peritonitis and necrotizing fasciitis models, Fernández-Bravo et al [188] used the mutants of T6SS and ExoA of these strains to elucidate the possible role in mixed infections and demonstrated that both virulence factors play a role after monomicrobial and polymicrobial infection.…”
Section: Aeromonas In Human Infectionsmentioning
confidence: 99%
See 4 more Smart Citations
“…They suggested that the type six secretion system (T6SS) and exotoxin A (ExoA) were involved in this complex infection. Recently, using a mouse peritonitis and necrotizing fasciitis models, Fernández-Bravo et al [188] used the mutants of T6SS and ExoA of these strains to elucidate the possible role in mixed infections and demonstrated that both virulence factors play a role after monomicrobial and polymicrobial infection.…”
Section: Aeromonas In Human Infectionsmentioning
confidence: 99%
“…Wound infections due to Aeromonas can progress severely to necrotizing fasciitis (NF), usually in immunocompromised patients [5,211]. NF is commonly known as a flesh-eating disease that can cause hypotension, fever, necrosis, and gangrene and can be a life-threating infection [156,[186][187][188]211]. A. hydrophila is the Aeromonas species most frequently associated in reported NF cases and in some cases, water was considered the source of infection [156,186,[211][212][213][214].…”
Section: Wound Infectionsmentioning
confidence: 99%
See 3 more Smart Citations